2011
DOI: 10.5271/sjweh.3186
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems and sickness absence among middle-aged employees

Abstract: Objective The aim of this study was to examine whether sleep problems predict subsequent sickness absence among middle-aged public sector employees. MethodsThe data included 5391 female and 1454 male employees of the City of Helsinki from questionnaire surveys at baseline in [2000][2001][2002]. These data were prospectively linked to the employer's sickness absence register data, with a mean follow-up time of 4.1 years. Using Poisson regression analysis, we examined associations between sleep problems (none, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 31 publications
2
40
0
2
Order By: Relevance
“…Furthermore, health risks indicated by work disability, for example, are higher for frequent as compared to occasional insomnia symptoms [18,19,62]. In order to promote better health and well-being, our results also highlight the importance to focus on the milder insomnia-related symptoms as well as the more serious ones.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Furthermore, health risks indicated by work disability, for example, are higher for frequent as compared to occasional insomnia symptoms [18,19,62]. In order to promote better health and well-being, our results also highlight the importance to focus on the milder insomnia-related symptoms as well as the more serious ones.…”
Section: Discussionmentioning
confidence: 71%
“…The response alternatives were reclassified into three groups: no (answering modes ‘not at all’ and ‘a little’), occasional (answering mode ‘to some extent’), and frequent (answering modes ‘quite often’ and ‘very often’). Three categories were formed to be able to better show a gradient in the associations between sociodemographic and socioeconomic factors and insomnia symptoms, and because even milder and occasional symptoms are related to poorer health and work ability [18,19]. In addition to insomnia-related symptoms, frequency of hypnotic use was requested.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were echoed in the study by Bultmann and colleagues (2013) 3 , who found that in the Danish Work Environment Cohort Study, sleep disturbances and fatigue significantly predicted sickness absence. Rahkonen and colleagues (2012) 4 examined data from employees of the City of Helsinki and found that frequent sleep problems were associated with increased sickness absences, both short and long in duration. Rajaratnam and colleagues (2011) 5 found that police officers with probable sleep disorders were more likely to miss work as well.…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies have shown clear associations between sleep problems and long-term sick leave or disability retirement [4][5][6][7][8][9][10][11]. Musculoskeletal disorders and mental illness were often implicated [9,10].…”
Section: Introductionmentioning
confidence: 99%